2020
DOI: 10.1186/s12936-020-03444-w
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Olyset® Net on Plasmodium falciparum infection after three years of distribution in western Kenya

Abstract: Background Several types of insecticides, treating technologies and materials are available for long-lasting insecticide-treated nets (LLINs). The variations may result in different efficacies against mosquitoes and correspondingly infection risks for the Plasmodium falciparum malaria parasite. This cross-sectional study investigated whether infection risk varied among children who slept under different LLIN brands in rural villages of western Kenya. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…population. 57 At the least, standard-LLINs are able to reduce physical contact between humans and mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…population. 57 At the least, standard-LLINs are able to reduce physical contact between humans and mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Secondly, since the previous studies did not use an insecticide-treated fabric (Kirby et al ., 2009 ; Getawen et al ., 2018 ), we used a fabric which is incorporated with 2% permethrin (Olyset ® Net, Sumitomo Chemical, Tokyo, Japan) (Tamari et al ., 2020 ). A study in Brazil reported that Anopheles darlingi females prefer to rest on the ceilings (Roberts et al ., 1987 ), and a study in the present study area observed that vectors prefer to rest in the upper part of house (Kawada et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%